Stand Up Comedy Dan Kritik Sosial Di Indonesia (Analisis Wacana Pada Abdurrahim Arsyad) - Kesiya Agustina; Indrawati (Jurnal Pendidikan Sosial Dan Konseling, 2023)
Stand up Comedy is a genre in comedy, where someone perfoms monologue wih the main aim making people laugh. However, it cannot be denied that stand up comedy can also be used be other purpose, such as democracy and expressing opinions and critism. The comedian actively presents critical material in every performance, Abdurrahim Arsyad, often includes his critism in every stage act. Thesis entitled “Stand Up Comedy and Critism in Indonesia ( DiscourseAnalysis of Andurrahim Arsyad)” in the research the authot took in qualitative research method approach. Using critical discourse analysis techniques from Teun Van A. Dijk. The analyze the content of the text in Abdurrahim Arsyad stand up comedy video entitled “Democracy is Comupted and Unque Language in Indonesia” analyzing the macro structure, micro structure, superstructure. The data collection tehniques in this research arw documentation tehniques and listening and note taking tehniques. The results of the setting research obtained from Abdur’s two stand up videos above include critism policies that are not in line with what society wants.